The Role of Language in the Identity Formation of Transnational EFL Teachers - Perla Villegas-Torres; Irasema Mora-Pablo (Asociación Colombiana de Profesores de Ingles, 2018)
This research report presents the results of a qualitative study carried out at the Universidad de Guanajuato in central Mexico. Its purpose was to examine the process of identity formation of return migrants who lived a number of years in the United States and are currently studying for a BA in TESOL in Mexico. The participants use their knowledge of the English language to be able to reinsert themselves in society once they have returned to live in the country. Through narrative inquiry using autobiographies and semi-structured interviews, the study focuses on how language might influence the way in which individuals perceive themselves. Implications on family, ethnic associations, and school experiences were found.